Hubungan Antara Pola Makan Dengan Hipertensi Pada Lansia Di Desa Risa: Relationship Between Diet And Hypertension To The Elderly In The Village Of Risa - Jannah, Nurul (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The diet that causes hypertension is the diet of older people that consumes sugar, raising, high salt,excessive fatsuch as heavy coconut mmilk, oil,vagetables and other gas-filled friutsand beverange consumed daily, such as coffe. The study was intended to shed light on the relationship between diet and hypertension in the elderly in the village of Risa. Research methods used by cross sesctional with sesctional engineering. The sampling used is 40 respondents about the distribution of respondents based on low diet with hypertensive concerns in the village of Risa, low 0 respondents (0.0%). Moderate diet with the incidence of hypertension, 0 respondents (0.0%). High diet with hypertension incident, 3 respondents (9.7%). Lower 4 respondents (66.7%). Diets are current with the incidence of hypertensions being 3 (100%). High diet with the incidence of hypertension, 20 high(64.5%), then lower 2 (33.3%). Moderate diet with incidence of hypertension, 0 respondents (0.0%). High diet with hypertension 8 respondents (25.8%). Studies obtained no correlation between diet and hypertension in the elderly is p=0.680<0.05. Which mean there’s no link between diet and hypertension in the elderly in Risa village and p=0.680”. The conclusion for research on the relationship between diet and hypertension in the village of Risa concludes: “there’s no link between diet and hypertension in the elderly in Risa village and p=0.680”.